A problem of limited-access special lanes. Part II: Exploring remedies via simulation. (October 2015) - Cassidy, Michael J.; Kim, Kwangho; Ni, Wei; Gu, Weihua
Highlights: Computer simulation is used to explore several bottleneck remedies. Redesigning access points in select ways can lessen bottleneck severity. Greatest improvements came by removing physical barriers to special-lane access. Legislation to limit carpool-lane operating times produced unintended consequences. Abstract: Spatiotemporal analyses of freeway sites in Part I have shown that special-lane access points are prone to become bottlenecks. These can degrade traffic flows, sometimes in all lanes. Part II explores select impacts of re-designing the means of entering and exiting a special lane, and of altering the policy governing its use. Parametric tests were conducted using a computer simulation model that was calibrated to one of the sites studied in Part I; one with a buffer-separated carpool lane. Though less reliable than what might have been observed via experiments in real settings, the simulated findings seem to offer useful insights nonetheless. The findings indicate that traffic conditions would improve at the site by elongating the carpool lane's buffer opening beyond its present length of 400 m. Yet, only modest improvements were predicted, even when the opening was elongated to 1000 m or more. Greater benefits were predicted from disentangling the movements made into and out of the carpool lane. This was achieved by placing first a buffer opening to serve only ingress, followed by another immediately downstream to serve egress. The benefits of this treatment were again limited, even when each tandem opening was elongated to a length of 700 m. Fully removing the buffer that physically separates the carpool lane from the regular ones was predicted to bring the greatest improvements to traffic. Also examined was pending legislation that would leave the carpool-lane buffer in place, while limiting the times of day when the lane is reserved for special use. Simulations predict that this legislation would degrade travel conditions below those that presently occur at the site. The extent of this predicted degradation varied, depending upon the time of day when the lane-use restriction went into effect.